Determination of acid sites in porous aluminosilicate solid catalysts for aqueous phase reactions using potentiometric titration method - Yu K; Kumar N; Aho A; Roine J; Heinmaa I; Murzin DY; Ivaska A (Academic Press INC Elsevier Science, 2025)
A potentiometric acid base titration method was developed to characterize the acid base properties of H-Beta-25, H-Beta-300, H-Ferrierite-20 and Si-MCM-48 zeolites in aqueous solutions. The method is based on linearization of the titration curve. The zeolite powders were dispersed in a sodium nitrate solution which was then titrated with a standard solution of sodium hydroxide. Various acid sites were found in the studied zeolites, and both the protonation constants and the concentrations of these acid sites were determined. The chemical composition (aluminum and silicon), distribution of the aluminum sites, crystallinity as well as the acidic properties of the titrated zeolites were compared with those of the pristine zeolites by using Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES), X-ray Diffraction (XRD), Al-27 NMR spectroscopy and the commonly used gas phase Fourier Transform Infrared spectroscopy (FTIR) of pyridine adsorption method. (C) 2015 Elsevier Inc. All rights reserved.